Stainless steel promoted the electrochemical oxidation of amines into imines. (16th May 2022) - Lee, Keunyoung; Choi, Hyebin; An, Jaun; Kwon, Ki‐Young
Abstract: We report the electrochemical oxidation of benzylamine (BA) into the imine by applying a bare stainless steel mesh (SSM) as an anode. Scanning electron microscopy (SEM) and energy‐dispersive X‐ray spectroscopy (EDX) elemental mapping analysis confirmed that there was no corrosion on the surface of SSM after an anodic electrolysis. Based on the gas chromatography (GC) analysis and electrochemical results, it was confirmed that conversion of BA with SSM was approximately 3.3 times higher than with Pt electrode. This work suggests that the anodic electrolysis with a bare SSM could be a promising route to electrochemical oxidation of BA in the absence of oxidizing agents. Abstract : A stainless steel mesh (SSM) as an anode was utilized for electrochemical oxidation of benzylamine (BA). SSM showed higher conversion of BA than conversion of BA by Pt plate.